Effects of irisin on the dysfunction of blood–brain barrier in rats after focal cerebral ischemia/reperfusion - Guo, Peipei (Brain Behav, 2019)
OBJECTIVE: To investigate whether irisin could protect against blood–brain barrier (BBB) dysfunction following focal cerebral ischemia/reperfusion in rats. METHODS AND MATERIALS: Seventy‐two adult male Sprague Dawley rats weighing 280–320 g were randomly divided into three groups: sham operation group (S), focal cerebral ischemia/reperfusion group (FC), and irisin group (IR). Focal cerebral ischemia was induced by improved thread occlusion of right middle cerebral artery (MCAO) for 2 hr followed by reperfusion for 24 hr in rats. After 24 hr of reperfusion, the neurological evaluation was performed by the method of Longa's score. The histopathological changes were observed by HE staining. The brain water content was determined by detecting the wet weight and dry weight. The BBB permeability was assessed by fluorescence spectrophotometer and fluorescence microscopy for Evans blue (EB) extravasation. The activity and expression of matrix metalloproteinase‐9 (MMP‐9) in different groups were detected by immunohistochemical staining, Western blot, and gel gelatin zymography. RESULTS: After MCAO, the neurological deficit scores, the infarct volume, the brain water content, and the EB content were higher in the FC group than those in the S group (p < .05). While after irisin treatment, these indicators mentioned above were lower than those in the IR group (p < .05). Moreover, the protein expression of MMP‐9 in the cortex increased significantly after MCAO, while irisin treatment could decrease the protein expression of MMP‐9 in the cortex (p < .05). CONCLUSION: Our data suggest that irisin can attenuate brain damage both morphologically and functionally and protect BBB from disruption after focal cerebral ischemia/reperfusion, which is highly associated with the inhibition of the expression and activity of MMP‐9 in the brain tissue.